CREATING DEMOCRATIC POLITICAL CONSCIOUSNESS FOR THE PEOPLE IN THE OPERATIONS OF PHETCHABURI MUNICIPALITY, PHETCHABURI PROVINCE - Mee-Anek, SM1 Sukontee; Kettong, Dawnapa; Phalakula, Anucha (Journal of MCU Phetchaburi Review, 2025)
This mixed-method research aimed to 1) study the level of democratic political consciousness development among the public; 2) compare public opinions on democratic political consciousness development among the public, classified by individual factors; and 3) propose the development of democratic political consciousness among the public through the application of the six Saraniyadhamma principles. The sample consisted of 393 residents in Phetchaburi Municipality aged 18 years and over and 9 key informants. Data were analyzed using percentages, means, standard deviations, F-tests, one-way ANOVA, and descriptive content analysis. The results revealed: 1) The overall level of democratic political consciousness development was high; 2) A comparison of public opinions on democratic political consciousness development among the public, classified by individual factors, revealed that differences in individual factors, including age and education level, significantly influenced the development of democratic political consciousness at the 0.05 level; and 3) The development of democratic political consciousness through the application of the six Saraniyadhamma principles consisted of: (1) Metta-kaya-karma, which promotes right and beneficial actions for others. To create awareness of rights and duties and promote political morality (2) Metta Vacīkarma: Use constructive, reasonable and kind words to create mutual understanding in political society (3) Metta Manokarma: Promote respect for different opinions, have good intentions and cooperate in developing the community under the law (4) Sathaṇobhāki: Focus on the common good, use public resources with value for the benefit of the community (5) Sīla Samanyata: Instill responsibility in duties, maintain discipline, respect the rights and freedoms of others (6) Ditthi Samanyata: Be open to listening to the opinions of all parties in order to create consensus and good attitudes towards each other in living together peacefully.